Influence of titanium and oxygen vacancies on the transport and conducting properties of barium titanate. Issue 2 (7th October 2015) - Zulueta, Y. A.; Dawson, J. A.; Leyet, Y.; Guerrero, F.; Anglada‐Rivera, J.; Nguyen, M. T.
Abstract : The transport and conducting properties of oxygen and titanium deficient cubic barium titanate (BT) were studied using atomistic simulations. The thermal expansion coefficient is shown to decrease when the number of titanium and oxygen vacancies increases. The influence of point defect concentration on the diffusion and conduction activation energies is determined, and the values are in good agreement with available experimental results. We also considered the defect energetics for formation of Ti and O vacancies using two proven interatomic potential models. Lattice static simulations reveal that strong binding energies exist for the trimer defect arrangement of V O − V Ti − V O, and that they are similar to the formation enthalpy of rutile TiO2, implying that a strong driving force for the formation of this cluster defect is present. The results reported here can provide some helpful guidelines for optimization of the properties and functionalities of BT based on titanium and oxygen vacancies.